The Repeat Rent Index - Ambrose, Brent W.; Coulson, N. Edward; Yoshida, Jiro (The Review of Economics and Statistics, 2015)
We employ a weighted repeat rent estimator to construct quarterly indexes that expand the profession’s ability to make cross-sectional comparisons of housing markets. Our analysis shows that there is considerable heterogeneity in the behavior of rents across cities over the 2000–2010 decade, but the number of cities and years for which nominal rents fell is substantial; rents fell in many cities following the onset of the housing crisis in 2007; and the repeat rent and Bureau of Labor Statistics indexes differ due to sampling and construction methods.